Characteristics of T‐cell responses in COVID‐19 patients with prolonged SARS‐CoV‐2 positivity – a cohort study - Yang, Jingyi (Clin Transl Immunology, 2021)
OBJECTIVE: SARS‐CoV‐2 has caused a worldwide pandemic of COVID‐19. The existence of prolonged SARS‐CoV‐2 positivity (PP) has further increased the burden on the health system. Since T cells are vital for viral control, we aimed to evaluate the characteristics of T‐cell responses associated with PP. METHODS: We established a PP cohort and two age‐ and sex‐matched control cohorts: a regular clinical recovery (CR) cohort and a healthy donor (HD) cohort. The mean time for RNA negativity conversion in the PP cohort was markedly longer than that in the CR cohort (66.2 vs 25.3 days), while the time from illness onset to sampling was not significantly different. T‐cell responses in the PP cohort were assayed, analysed and compared with those in the CR and HD cohorts by flow cytometry and ELISpot analysis of peripheral blood mononuclear cells. RESULTS: Compared with the CR cohort, the proliferation, activation and functional potential of CD8(+) and CD4(+) T cells in the PP cohort were not significantly different. However, the frequencies and counts of Teff and Tem in CD8(+) but not in CD4(+) T cells of the PP cohort were prominently lower. Moreover, a weaker SARS‐CoV‐2 N protein‐specific IFN‐γ(+) T‐cell response and a higher frequency of Tregs were detected in the PP cohort. CONCLUSION: Suppressed CD8(+) T‐cell differentiation is associated with PP and may be an indicator for the prediction of prolonged SARS‐CoV‐2 positivity in COVID‐19 patients. The association between suppressed CD8(+) T‐cell differentiation and elevated Tregs warrants studies in the future.